2017
DOI: 10.1103/physrevfluids.2.024601
|View full text |Cite
|
Sign up to set email alerts
|

Helicity statistics in homogeneous and isotropic turbulence and turbulence models

Abstract: We study the statistical properties of helicity in direct numerical simulations of fully developed homogeneous and isotropic turbulence and in a class of turbulence shell models. We consider correlation functions based on combinations of vorticity and velocity increments that are not invariant under mirror symmetry. We also study the scaling properties of high-order structure functions based on the moments of the velocity increments projected on a subset of modes with either positive or negative helicity (chir… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
17
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 41 publications
0
17
0
Order By: Relevance
“…More broadly, we conjecture that the phenomenon of scale-dependent phase alignment uncovered in this work may be the mechanism underpinning the joint forward cascade of two ideal invariants in other physical systems, including nonconducting fluids described by the Navier-Stokes equation [22,24,26,27].…”
mentioning
confidence: 81%
“…More broadly, we conjecture that the phenomenon of scale-dependent phase alignment uncovered in this work may be the mechanism underpinning the joint forward cascade of two ideal invariants in other physical systems, including nonconducting fluids described by the Navier-Stokes equation [22,24,26,27].…”
mentioning
confidence: 81%
“…By forcing at large scales the dNS equations, a direct helicity cascade with E(k) ∼ ǫ 2/3 H k −7/3 was obtained. It was also notably shown that as soon as helicity is not made strictly sign-definite, by adding helical Fourier modes with the opposite helicity (negative here), the inverse energy cascade vanishes, and that the transition between the upward and forward cascades mechanisms looks singular [14,16]. On the other hand, by changing the relative weight of homochiral and heterochiral triads, one is led to a transition from direct to inverse cascade for a finite value of the control parameter [15], showing that the way Navier Stokes equations transfer energy across scales might be strongly different by changing the involved degrees of freedom.…”
Section: Introductionmentioning
confidence: 92%
“…They consequently recovered the second scenario of [3], namely an inverse cascade of kinetic energy and a forward cascade of helicity, showing that all three dimensional turbulent flows indeed possess a sub-set of Fourier interactions potentially able to sustain an inverse energy cascade. Such a "surgery" of the Navier-Stokes equations was thoroughly investigated in multiple subsequent works [14][15][16] so that the details are not recalled here. The main findings are that by forcing at small scales the decimated Navier-Stokes (dNS) equations where helicity is made sign-definite, say positive here, kinetic energy is transferred to smaller wavenumbers with E(k) ∼ ǫ 2/3 k −5/3 .…”
Section: Introductionmentioning
confidence: 99%
“…By employing the conventional turbulence time scale ω k ∝ ε 1/3 k 2/3 , (1.2a,b) provides the conventional simultaneous or joint energy and helicity cascades range spectra (Brissaud et al 1973), (1.3a,b) where C K and C H are constants. The spectra provided by (1.3a,b) are observed in the numerical simulations of homogeneous turbulence (Borue & Orszag 1997;Chen et al 2003a,b;Mininni, Alexakis & Pouquet 2006;Baerenzung et al 2008;Sahoo, De Pietro & Biferale 2017), an observation of an atmospheric boundary layer (Koprov et al 2005), and a direct numerical simulation (DNS) of the Ekman boundary layer (Deusebio & Lindborg 2014). It should be noted that Linkmann (2018) suggested the possibility of helicity altering the value of C K , which poses a question on the universality of Kolmogorov's theory.…”
Section: Introductionmentioning
confidence: 96%
“…2003 a , b ; Mininni, Alexakis & Pouquet 2006; Baerenzung et al. 2008; Sahoo, De Pietro & Biferale 2017), an observation of an atmospheric boundary layer (Koprov et al. 2005), and a direct numerical simulation (DNS) of the Ekman boundary layer (Deusebio & Lindborg 2014).…”
Section: Introductionmentioning
confidence: 99%